Hot embossed microtopographic gradients reveal morphological cues that guide the settlement of zoospores - Xiao, Linlin; Grunze, Michael (Langmuir, 2013)
Among different surface cues, the settlement of cells and larvae of marine macrofouling organisms has been found to be strongly influenced by surface microtopographies. In this article, the settlement of zoospores of the green alga Ulva linza on a surface topographic gradient has been investigated. “Honeycomb” gradient structures with feature sizes ranging from 1 to 10 μm were prepared by hot embossing, and the effect on the density of spores that attached in settlement assays was quantified. The highest density of spores was found when the size of the microstructures was similar to or larger than the size of the spores. With decreasing size of the structures, spore settlement density decreased. Interestingly, spore settlement density correlated with the Wenzel roughness of the surfaces. “Kink sites” on the surface played an important role and resembled preferred attachment positions. Furthermore, the gradients allowed the minimum pit size that the spores were able to squeeze into to be determined.